Application of Kano model management combined with standardized skin care in preventing incontinence-associated dermatitis in patients with acute stroke - QIU Songwang; ZHAO Xiaohong (Pifu-xingbing zhenliaoxue zazhi)
[Objective] To explore the application of Kano model management combined with standardized skin care in preventing incontinence-associated dermatitis in patients with acute stroke. [Methods] Ninety patients with acute stroke admitted to the First Affiliated Hospital of Xiamen University from January to December 2021 were divided into two groups using a random number table method. The control group (45 cases) received routine care, while the observation group (45 cases) received the Kano model management in combination with standardized skin care. Nursing care was given to both groups until discharge. The incidence of incontinence-associated dermatitis, quality of life, and the degree of satisfaction were compared between the two groups. [Results] The incidence of incontinence-associated dermatitis was significantly lower in the observation group (8.89%) than in the controls (35.55%) (χ2=9.26, P=0.002). Moreover, the Kolcaba Comfort Scale (GCQ) scores in all dimensions were higher in the observation group than in the control group (all P<0.001). In addition, newcastle satisfaction with nursing scale was higher in the observation group (95.56%) than in the control group (82.22%) (χ2=4.05, P=0.044). [Conclusions] The combination of Kano model management and standardized skin care can effectively prevent the development of incontinence-associated dermatitis and improve patients′ comfort and satisfaction scales of the patients′ family members in subjects with acute stroke.